RESIDUAL SOLUBILITY OF SF-GROUPS (Journal of Sciences, Islamic Republic of Iran)
Seifert Fibre Groups (SF-Gps) have been introduced and their first derived groups have been worked out in an earlier paper by the author [2,3]. Now we aim to prove that they are residually soluble and residually finite.